2022
DOI: 10.3390/educsci12110743
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Teachers’ Strategies in Solving Absolute Value Equations and Inequalities

Abstract: Many secondary school students have encountered difficulties when dealing with absolute value equations and inequalities. This condition might be brought to higher education, including by pre-service mathematics teachers in teacher training colleges. The difficulties in dealing with absolute value equations and inequalities, which can be observed from solution strategies, indicate the lack of symbol sense. This study aims to investigate strategies that pre-service teachers used while solving absolute value equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Many researchers have found that the roots of this misunderstanding among preservice teachers have been meticulously explored. Pre-service mathematics teachers in Indonesia use three different solution strategies for solving absolute value equations and inequalities, indicating a need for improved symbol sense in higher education (Jupri et al, 2022). Pre-service teachers' conceptual structures in absolute and quadratic inequalities are often incorrect, negatively impacting their mathematics teaching and learning and potentially inappropriately applied in daily life (Ali & Wilmot, 2016).…”
Section: Infinitymentioning
confidence: 99%
“…Many researchers have found that the roots of this misunderstanding among preservice teachers have been meticulously explored. Pre-service mathematics teachers in Indonesia use three different solution strategies for solving absolute value equations and inequalities, indicating a need for improved symbol sense in higher education (Jupri et al, 2022). Pre-service teachers' conceptual structures in absolute and quadratic inequalities are often incorrect, negatively impacting their mathematics teaching and learning and potentially inappropriately applied in daily life (Ali & Wilmot, 2016).…”
Section: Infinitymentioning
confidence: 99%
“…Previous researchers have discussed absolute value (Almog & Ilany, 2012;Amram et al, 2019;Ciltas & Tatar, 2011;Curtis, 2016;El-khateeb, 2016;Elia et al, 2016). Student's difficulties in solving absolute value problems allow for differences in students' metacognitive awareness in solving absolute value problems.…”
Section: Introductionmentioning
confidence: 99%